2020
DOI: 10.1101/2020.06.14.20129957
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Age-dependent assessment of genes involved in cellular senescence, telomere and mitochondrial pathways in human lung tissue of smokers, COPD and IPF: Associations with SARS-CoV-2 COVID-19 ACE2-TMPRSS2-Furin-DPP4 axis

Abstract: Aging is one of the key contributing factors for chronic obstructive pulmonary diseases (COPD) and other chronic inflammatory lung diseases. Cigarette smoke is a major etiological risk factor that has been shown to alter cellular processes involving mitochondrial function, cellular senescence and telomeric length. Here we determined how aging contribute to the alteration in the gene expression of above mentioned cellular processes that play an important role in the progression of COPD and IPF. We hypothesized … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 61 publications
(75 reference statements)
0
5
0
Order By: Relevance
“…The ratio of AT 1 R to AT 2 R increased five to six fold in bronchiole areas with enhanced fibrosis, which were associated with diminished lung function in COPD patients (Bullock et al, 2001). A recent study also showed that sub-chronic e-Cig exposure enhances lung inflammation and ACE2 expression which were shown to be mediated by α7 nAChRs (Wang et al, 2020c disorders in association with COVID-19 infection (Maremanda et al, 2020). These results indicate that smokers and/or vapers may have an increased risk of COVID-19 related complications which can aggravate disease severity and treatment outcome.…”
Section: Lungmentioning
confidence: 94%
“…The ratio of AT 1 R to AT 2 R increased five to six fold in bronchiole areas with enhanced fibrosis, which were associated with diminished lung function in COPD patients (Bullock et al, 2001). A recent study also showed that sub-chronic e-Cig exposure enhances lung inflammation and ACE2 expression which were shown to be mediated by α7 nAChRs (Wang et al, 2020c disorders in association with COVID-19 infection (Maremanda et al, 2020). These results indicate that smokers and/or vapers may have an increased risk of COVID-19 related complications which can aggravate disease severity and treatment outcome.…”
Section: Lungmentioning
confidence: 94%
“…Likewise, the lung samples were procured from three sources; (a) commercially available resource for procurement of human tissue and organ-NDRI (National Disease Research Interchange), (b) NHLBI-funded bio-specimen repository-LTRC (Lung Tissue Research Consortium), and (c) Department of Medicine and Pathology at the University of Helsinki Hospital, Finland as reported previously (31, 32).…”
Section: Methodsmentioning
confidence: 99%
“…Heat shock protein Involved in pulmonary disease as differential expression gene (Maremanda et al, 2020).…”
Section: Hspd1mentioning
confidence: 99%
“…Consistent with our findings, ANGPT2 was upregulated in several inflammatory diseases and took part in the direct regulation of inflammationrelated signal pathways in PAH (Zhong et al, 2018). Differential expression of HSPD1, involved in mitochondrial biogenesis, was noted in patients suffering from pulmonary diseases compared with normal controls (Maremanda et al, 2020). Interaction of HSPH1 with STAT3 may enhance its phosphorylation, which exacerbated pulmonary inflammation in acute lung injury, though there is no such report relating to PAH (Liang et al, 2020).…”
Section: Hsa-mir-106b-5pmentioning
confidence: 99%
See 1 more Smart Citation